Distribution of AMPA-type glutamate receptor subunits in the chick visual system - R.S. Pires; L.R.G. Britto (Brazilian Journal of Medical and Biological Research, 1997)
Several glutamate receptor (GluR) subunits have been characterized during the past few years. In the present study, subunit-specific antisera were used to determine the distribution of the AMPA-type glutamate receptor subunits GluR1-4 in retinorecipient areas of the chick brain. Six white leghorn chicks (Gallus gallus, 7-15 days old, unknown sex) were deeply anesthetized and perfused with 4% buffered paraformaldehyde and brain sections were stained using immunoperoxidase techniques. The AMPA-type glutamate receptor subunits GluR1, GluR2/3 and GluR4 were present in several retinorecipient areas, with varying degrees of colocalization. For example, perikarya in layers 2, 3, and 5 of the optic tectum contained GluR1, whereas GluR2/3 subunits appeared mainly in neurons of layer 13. The GluR4 subunit was only detected in a few cells of the tectal layer 13. GluR1 and GluR2/3 were observed in neurons of the nucleus geniculatus lateralis ventralis, whereas GluR4 was only present in its neuropil. Somata in the accessory optic nucleus appeared to contain GluR2/3 and GluR4, whereas GluR1 was the dominant subunit in the neuropil of this nucleus. These results suggest that different subpopulations of visual neurons might express different combinations of AMPA-type GluR subunits, which in turn might generate different synaptic responses to glutamate derived from retinal ganglion cell axons